2010
DOI: 10.1128/mcb.01089-09
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Hedgehog-Dependent Full-Length Gli3 Accumulation in Primary Cilia and Subsequent Degradation

Abstract: Localization occurs within minutes of Hh addition, making it the fastest reported readout of pathway activity, which permits more precise temporal and spatial localization of Hh signaling events. We show that the species of Gli3 that accumulates at cilium tips is full-length and likely not protein kinase A phosphorylated. We also confirmed that phosphorylation and ␤TrCP/Cul1 are required for endogenous Gli3 processing and that this is inhibited by Hh. Surprisingly, however, Hh-dependent inhibition of processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
281
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(305 citation statements)
references
References 100 publications
(128 reference statements)
14
281
5
Order By: Relevance
“…Despite previous in vitro data suggesting an important role of Spop in Gli2 degradation (18)(19)(20)(21)23), the level of Gli2 was not significantly changed in Spop mutants (Fig. 4C).…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…Despite previous in vitro data suggesting an important role of Spop in Gli2 degradation (18)(19)(20)(21)23), the level of Gli2 was not significantly changed in Spop mutants (Fig. 4C).…”
Section: Resultscontrasting
confidence: 47%
“…Previous in vitro studies found that Spop inhibited Hh signaling by targeting Gli2 and Gli3FL for degradation (18)(19)(20)(21)23). To test whether Ihh signaling was affected by the loss of Spop, we examined the expression of Patched 1 (Ptch1), a direct transcriptional target of Ihh, in E13.5 forelimbs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the relative efficiency with which these two Gli forms are specifically proteolyzed that distinguishes the inactive versus the active hedgehog signaling state. In the absence of activated Smo, Gli2 and 3 proteins traffic into primary cilium where they are modified into repressor forms [41]. This process is initiated by a series of sequential phosphorylations, initiated by protein kinase A and then followed by glycogen synthase kinase-3-β and casein kinase 1.…”
Section: Overview Of the Hedgehog Signaling Pathwaymentioning
confidence: 99%
“…For the target cell, hedgehog signaling can be facilitated by the presence of heparin proteoglycans and lower affinity hedgehog coreceptor proteins that include CDON and BOC [49]. Further downstream, integration of vertebrate hedgehog signaling into the primary cilium means that signal processing requires the activities of numerous ciliar transport proteins to shuttle Gli proteins into and out of the cilium [41,50,51]. Genetic ablation of individual ciliar transport proteins in mice confers phenotypes that are reiterative of mutations in the primary hedgehog regulatory genes.…”
Section: Overview Of the Hedgehog Signaling Pathwaymentioning
confidence: 99%